DAMPAK PENGGUNAAN MEDIA PEMBELAJARAN BERBASIS ICT TERHADAP HASIL BELAJAR PAI PESERTA DIDIK PADA SMK NEGERI 1 KOTA PAREPARE - Tanwir Tanwir; Abd Rahman F; Sulaeman Thaha (IAIN PAREPARE, 2018)
The main issue of this article is the successful learning of studentsthrough the use of information and communication technology (ICT)based PAI learning media at SMKN Parepare. This article is to know theimpact of the use of ICT in PAI learning at SMK Negeri 1 Kota Parepare.The method used in this study is qualitative with the procedure ofcollecting data through: interviews, observation and documentation. Theinformants used as sources were all PAI teachers, Principals, KTU,several specified teachers, Computer Operators and students. Dataanalysis uses data reduction, presentation and verification. Data isverified using an estimation technique. This study shows that the use ofinformation and communication technology (ICT) based learning mediain PAI learning at State Vocational High School 1 in Parepare City hasrun optimally, and supports positivity, both for students, both forteachers, who use the equipment used to deliver messages -message oflearning from the sender to the recipient of the message so that it canhelp students' thoughts, feelings, concerns and interests occur andincrease the efficiency of the learning process.